INFORMATION TECHNOLOGY AS A MEANS OF TEACHING FOREIGN LANGUAGES - Khakimova Nasiba Turgunovna (Bright Mind Publishing, 2025)
This article describes the role and importance of information technology in education. It also discusses such issues as the choice of materials for language classes and issues related to effective information and communication technologies.
Keywords: Mental activity, distance learning, information technology, information search, information and communication technologies